Potential of waterbodies as a reservoir of Escherichia coli pathogens and the spread of antibiotic resistance in the Indonesian aquatic environment - Imam Megantara; Nova Sylviana; Putri Alia Amira; Gita Widya Pradini; Ita Krissanti; Ronny Lesmana (Journal of Water, Sanitation and Hygiene for Development, 2023)
River contamination remains a significant public health problem worldwide, including in Indonesia. In the community, rivers are water resources for many purposes. However, indiscriminate use of antibiotics in the veterinary and medical sectors, the community habit of throwing waste into the river, the inadequate removal of human medicine compounds in WWTP, and poor industrial waste management will induce the spread of pathogenic bacteria and antibiotic resistance between the environment and humans/animals. This review aims to analyse the various factors that influence the emergence of pathogenic Escherichia coli and antimicrobial resistance bacteria (ARB) in the aquatic environment, especially in Indonesia. In conclusion, pathogenic E. coli can adjust its physiological or metabolic conditions to survive in aquatic environments and was found resistant to antibiotics. Meanwhile, this study also describes the potency of the aquatic environment in Indonesia as a vector for the spread of pathogenic E. coli and the growth of ARBs, factors involved in the evolution and spread of antibiotic resistance in aquatic environments, and possible ways to curtail microbial risk to public health and the emergence and spread of antimicrobial resistance in the aquatic environment in Indonesia. HIGHLIGHTS Various rivers in Indonesia have the potential to become a reservoir of E. coli pathogens.; Various rivers in Indonesia are efficient vectors for the spread of antimicrobial resistance bacteria.; The antibiotic resistance can spread in the environment.; Pathogenic E. coli can adjust to survive in aquatic environments.; E. coli pathogens can facilitate the transfer of resistance genes between bacteria.;